Pemetaan Perkembangan Program Kampung Keluarga Berencana (KB) dengan Sistem Informasi Geografis di Kabupaten Sukabumi - Sumarni, Euis; Maryani, Enok; Sumantri, Lili (INNOVATICS: International Journal on Innovation in Research of Informatics, 2022)
One of Indonesia's problems is its rapid population increase. The population growth rate for Indonesia between 2010 and 2020 is 1.49%. North Sukabumi is a developing region of Sukabumi Regency with a greater population and population growth rate than Southern Sukabumi. Family Planning Village is one of the government's initiatives to address the issue of population increase. This research aims at assessing the growth of KB village areas and the evolution of the KB village program in North Sukabumi from 2017 to 2020. This study employs a descriptive quantitative GIS-based methodology. This study used scoring and weighting analysis to analyze its data. The growth of the KB village program in North Sukabumi from 2017 to 2020 is often shown on a map including two pieces of information: a diagram of the development of the KB village program each year and the percentage of the overall development of the KB Village program from 2017 to 2020. The findings of this research show that the number of KB villages continues to expand each year, with 94 KB villages existing by 2020. Furthermore, the growth of the KB village initiative in North Sukabumi between 2017 and 2020 is highly encouraging (60.90 %). This study is valuable to the government, KB village managers, and communities as it pertains to the improvement of family/community welfare via the KB Village program.